Brachytherapy in cervical cancer radiotherapy during COVID-19 pandemic crisis: problems and prospects - Miriyala, Raviteja; Mahantshetty, Umesh (Journal of Contemporary Brachytherapy, 2020)
COVID-19 pandemic has adversely affected general healthcare delivery systems and cancer care throughout the world. The management of locally advanced cervical cancer presents specific challenges in this context, especially brachytherapy and completion of radiotherapy treatment, without compromising the overall treatment time and anticipated outcomes. This article presents in detail the issues and possible solutions with currently available literature for COVID-19 and radiation, in particular brachytherapy management of locally advanced cervical cancers. The review attempts to provide possible explanations and pathways based on COVID-19 testing, brachytherapy processes including application, imaging, and fractionation, keeping in mind the overall treatment time.